Profil Usaha Pengolahan Kopi Bali Tugu Sari Pajahan di Desa Pajahan, Kecamatan Pupuan, Kabupaten Tabanan - SANG AYU DYAH ORCHID WULANDARI; I WAYAN WIDYANTARA; I DEWA GEDE AGUNG (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Business Profile of Bali Processing Coffee of Tugu Sari Pajahan in Pajahan Village, Pupuan Sub-District, Tabanan Regency. Tugu Sari Pajahan Bali Coffee Business is a coffee processing business that is accommodated by the Village Owned Enterprise. This study aims to determine theprofile, income, and marketing of Tugu Sari Pajahan Bali Coffee business. Thisresearch was conducted at Tugu Sari Pajahan Bali Coffee Business. The time of thisstudy was carried out for four weeks, namely in May to June 2018. The data used werequalitative and quantitative data with primary and secondary data sources and methodsof data collection by interview, documentation, and library research.The profile in thisstudy is a general description of Tugu Sari Coffee Business. The investment cost wasRp. 159,600,000.00, and the total cost used by Tugu Sari Coffee in 2017 was Rp.133,883,500.00. Tugu Sari's Bali Coffee business production usually produces anaverage of 10 tons in one year. The large net income of Tugu Sari Pajahan Coffeebusiness in 2017 was Rp. 45,225,950.00. Tugu Sari Pajahan Coffee Business in sellingits products is by using re-sellers and directly selling to shops, stalls, and mini marketsin the Tabanan, Denpasar, Badung and Buleleng areas.